Pengaruh Word Of Mouth terhadap Keputusan Mahasiswi Fisip Unsika Membeli Produk Kosmetik Hanasui Mattedorable Lip Cream Boba Edition - Hidayat, Zahra Rusydina; Kusumaningrum, Rastri; Teguh Santoso, Made Panji (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of Word of Mouth on the decision college students Faculty of Social Science and Political science Singaperbangsa Karawang University to buy the Hanasui Mattedorable Lip Cream Boba Edition cosmetic product. The research object is word of mouth as the (independent variable) and buying decisions as the (dependent variable) and use Elaboration Likelihood Model (ELM). The research method used is quantitative method with a survey design for 88 college students respondents who knew and had purchased the Hanasui Mattedorable Lip Cream Boba Edition cosmetic product. The questionnaire was used to measure how much influence word of mouth had on Unsika FISIP students in making purchasing decisions. The analysis technique used is Simple Linear Regression. The result of this research was that the word of mouth had a significant effect on purchasing desicision. Three variables that are believed to be indicators of word of mouth, namely discussing, recommending, encouraging. The research results of hypothesis testing recommend variables have no influence on purchasing decisions, while the variables discussing and encouraging influence purchasing decisions. Based on the results of the coefficient of determination test, it shows that word of mouth has a significant influence of 54.8% on purchasing decisions